STUDI EVALUASI MODEL DISCREPANCY PELAKSANAAN LAYANAN BIMBINGAN DAN KONSELING BIDANG PRIBADI SOSIAL - Umar, Nur Fadhillah (Universitas Negeri Makassar, 2018)
The purpose of this research was 1) understanding a discrepancy between the ideal standards and the result of implementations in the self-social field on SMKN 11 Malang. 2) Understanding how counselor’s teaching process on guidance units effectively on SMKN 11 Malang. 3) Undertanding counselor’s coup with the intention of school sopports for implementing the self-social services effectively on SMKN 11 Malang. Research metode which has used discrepancy evaluation model. It consisted of four stages such as planning, designing, implementing, and evaluating. The Result of the research shows that need assessment implementations in the self-social field has done successfully. However, in the implementation aspects, there were some parts which have not conducted. In the Collaboration aspects, most of school’s people got involved in the BK’s programs although collaboration between counselors and parents were not implemented superiorly